STUDY OF IEM CHARACTERISTICS IMPACT ON VANADIUM REDOX FLOW BATTERY PERFORMANCE - Khofanda, Joshua
Vanadium Redox Flow Battery (VRFB) is an electrical energy storage technology that produces chemical energy from the reduction-oxidation reaction of two vanadium-type electrolytes. One of the key components of VRFB is an ion exchange membrane (IEM). IEM is responsible for separating positive and negative half cells and preventing crosscontamination of vanadium ions while providing the ionic conductivity required by VRFB. As a key component, the IEM is expected to have high conductivity to produce high proton transfer rates and good selectivity to prevent vanadium cross-contamination of the two electrolytes. IEM has two main characteristics that influence other characteristics, namely ion-exchange capacity (IEC) and water uptake (WU). This study examines the impact of IEC, WU, and IEC/WU characteristics on electrochemical characteristics such as conductivity, vanadium permeability, and energy parameters (OCV/Time). From the results of the literature review shows that the increase in IEC and WU increases conductivity, vanadium permeability, and self-discharge rate (OCV/Time) while the increase in IEC/WU characteristics decreases conductivity, vanadium permeability, and self-discharge rate (OCV/Time). There are several membrane modification methods that have been reported that are able to increase the IEC and WU values of IEM membranes for VRFB applications. One modification method that is widely used is additive blending using nanoparticles as an additive. In general, nanoparticles that are hydrophilic, conductive, have high dispersibility, can interact with matrix functional groups to form a permselective barrier, and have good compatibility with polymer matrices, can be used as additives for VRFB membranes with good electrochemical characteristics. From the literature review, the addition of zirconium oxide nanotubes of 0.5%-weight on the sulfonated poly(arylene ether ketone) SPAEK membrane can produce IEC 1.27 meq/g and WU 79%. These values are the highest IEC and WU values that can be obtained by nanocomposite membranes for VRFB applications.